My house is your temple: An alternative vision of the architecture of the Kotosh Tradition - Siveroni, Viviana (2006)
Richard Burger has defined the "Kostosh Religious Tradition" (KRT) as an architectural tradition that assembles a number of presumably religious structures of the Late Preceramic and Forma ti ve Periode of the Central and North Highlands of Peru. The distinctive architectural feature of these KRT "temples" is a chamber with central hearth. Burger suggests that religious rituals staged in these structures provided an arena for social integration and expression of spiritual experience rather than for contestation, manipulation, and domination. Based on a comparative analysis of domestic architecture from the Early Formative site of Monte Grande, I propose that many of these presumably ritual structures may originally have been the residences of influential members of the early communities rather than temples. Sorne, particularly the larger ones, may have evolved into temples la ter on. This alterna ti ve interpretation of KRT architecture has profound implications for our understanding of the path to social complexity in the Forma ti ve Central Highlands of Peru.